Problems of functioning of Polish local action groups from the perspective of the social capital concept - Zajda, Katarzyna (Eastern European Countryside, 2024)
The LEADER approach was introduced in Poland as part of the LEADER+ Pilot Programme (implemented in the programming period 2004–2006) and, at present, it is being implemented as Axis 4 of the Rural Development Programme. Many researchers are interested in its progress. In their analyses, they use various concepts of social capital. It may be concluded on the basis of the studies published so far that local action groups are dominated by the public sector, whereas the economic sector is rather marginalised. Having taken into account the available publications, a team of sociologists from the University of Łódź conducted in 2011–2013 research devoted to the level and structure of social capital of local action groups. The study focused on organisations from 6 voivodeships which implemented scheme 2 of the LEADER+ Pilot Programme. The article presents the analyses of the most important problems of these organisations related to the condition of the components of social capital possessed by their members (partners). The researchers used the material from individual surveys completed by 573 respondents from 34 local action groups. It was proven that the surveyed organisations mainly cope with the problem of a low activity level of their members (partners), petrification of their boards and councils, marginalisation of representatives of the economic sector, high level of professionalization and low level of generalised trust among the persons who belong to these groups.